The Role of the Family Hope Program (PKH) Facilitator in Increasing Family Development Session in Sipungguk Village - Resdati (Institute of Computer Science (IOCS), 2021)
This study aims to describe the role of companions, inhibiting and supporting factors in the assistance of the Family Hope Program in Sipungguk Village, Kampar Regency. This research uses a qualitative approach, companion as the subject of the research. Interview, observation and documentation as data collection techniques. The validity of the data used triangulation of sources, methods and theories. The data analysis used an interactive cycle. The results showed that the assistant has four skill roles, namely the role of facilitative, educator, community representative and technical. Internal factors that become obstacles are the difficulty of participants to collect data files, and adapting to the new environment of the companion takes a long time. constraints, namely the distance traveled by the mentor to the mentoring place is quite far and the location of the mentor is in a narrow alley. The supporting factor is the enthusiasm of the beneficiaries and adequate facilities.